Evaluasi Kebijakan Pajak Pertambahan Nilai dengan Menggunakan Persepektif Publik Digital dalam Kerangka Public Value - Ferdian Al Ghifari Ganda Hutama; Annur Muhammad Rizki; Fadjar Tri Sakti (Universitas Sains dan Teknologi Komputer, 2026)
The policy to increase the Value Added Tax (VAT) rate to 12%, as stipulated in Law Number 7 of 2021 on the Harmonization of Tax Regulations, has generated diverse public responses, particularly regarding its impact on purchasing power, fiscal fairness, and policy legitimacy. This study aims to analyze public perceptions of the 12% VAT policy and assess the formation of public value using the Public Value framework. The research employs a mixed-methods approach with concurrent triangulation, combining quantitative sentiment analysis with qualitative content analysis of secondary data derived from public comments on Instagram. The findings indicate that public perception is predominantly negative, reflecting a low level of perceived policy value. Qualitative analysis further reveals that the VAT 12% policy is perceived as weak across the three dimensions of Public Value: policy benefits (value), legitimacy and public support (legitimacy and support), and governmental operational capacity (operational capabilities). The study concludes that the success of fiscal policy depends not only on legal validity and revenue objectives but also on the government’s ability to deliver tangible benefits, secure social legitimacy, and ensure effective implementation. Accordingly, this research recommends strengthening policy communication strategies, enhancing transparency and public participation, and improving economic mitigation mechanisms to increase public value and societal acceptance of the VAT 12% policy